Cybercrime - Grabosky, Peter N. (Keynotes in criminology and criminal justice series, 2016)
Acknowledgments -- About the author -- Preface -- Introduction -- A brief history of cybercrime -- A typology of computer crime -- Cybercrime explained -- Incidence, prevalence, distribution, and impacts -- Trends in cybercrime -- Investigation, prosecution, and sentencing -- Conclusion: the future of cybercrime and its control -- Endnotes -- References -- Appendix: useful websites relating to cybercrime -- Index